2000
DOI: 10.1046/j.1365-3083.2000.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Induced mRNA Expression of Interleukin‐5, but Not of Interleukin‐4 and Interferon‐γ, in Peripheral Blood Mononuclear Cells Obtained Before the Pollen Season Predicts the Clinical Efficacy of Immunotherapy for Seasonal Allergic Rhinitis

Abstract: The primary aim of this study was to investigate whether the allergen-induced synthesis of cytokines by peripheral blood mononuclear cells (PBMCs) obtained immediately before the pollen season could predict the clinical efficacy of immunotherapy during the following pollen season. PBMCs (1.0 x 106 cells/ml) were obtained from 17 nonatopic subjects and from 60 patients receiving immunotherapy for seasonal allergic rhinitis (caused by Japanese cedar pollens) immediately before the pollen season of 1998, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It was first recognized as a B-cell growth factor and among other properties, it enhances antigen presenting capacity of these cells and is essential for the IgE synthesis [ 33 , 34 , 35 ]. IL-5 levels have been found to be significantly increased in symptomatic subjects with allergic diseases [ 36 ]. Positive correlations have also been shown between the levels of eosinophil mediators and IL-5 and the symptoms of seasonal AR [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was first recognized as a B-cell growth factor and among other properties, it enhances antigen presenting capacity of these cells and is essential for the IgE synthesis [ 33 , 34 , 35 ]. IL-5 levels have been found to be significantly increased in symptomatic subjects with allergic diseases [ 36 ]. Positive correlations have also been shown between the levels of eosinophil mediators and IL-5 and the symptoms of seasonal AR [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is an important factor for the proliferation and activation of eosinophils after exposure to certain allergens such as OVA and pollen (81,82). A recent study found that mRNA expression for IL-5 was significantly lower in patients who had no nasal symptoms when compared with those who required medicines to control allergic symptoms during pollen season (83). Two human studies found that exposure to DEPs resulted in increased levels of IL-5 (65,84).…”
Section: Influence On Cytokine Expressionmentioning
confidence: 99%
“…AR is related to nasal mucus eosinophilia and increased IL-5 levels [23]. Previous studies have reported that IL-5 is increased in nasal mucosa of patients after their exposure to allergen and that IL-5 is closely correlated to eosinophilic inflammation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, cytokines derived from Th2 cells, which include IL-5 are involved in IgE synthesis and allergic inflammation. Recently, IL-5 has been shown to be involved in allergic inflammation and airway hypersensitiveness [26,38]. In addition, IgE has also been implicated in development of allergic disease and recruitment or accumulation of inflammatory cells such as eosinophils [39,40].…”
Section: Discussionmentioning
confidence: 99%